"Sawātiʿ al-Ilhām li Abī al-Fayd Fayḍī: Characteristics of the Tafsīr and the Neglected Style – An Analytical and Rhetorical Study" - Muhammad Yasin; Dr Abdul Majid Baghdadi; Munawar Ali Shah (Journal of Religion and Society, 2025)
This article reviews the book “Sawati Al-Ilham by Abu Al-faiz Faizi” as a unique experiment in Qur'anic exegesis through "Dotless style," a linguistic mode devoid of the use of diacritical marks. The research highlights linguistic creativity and rhetorical challenges that reflect the flexibility of the Arabic language, demonstrating its expressive capacity even under strict formal constraints. The exegesis incorporates a mystical Sufi perspective that transcends the apparent meaning of the Qur'anic text, seeking to uncover its deeper, esoteric dimensions. The article discusses the stylistic features of the book, such as its fluidity, precise linguistic analysis, and beautiful expression. It also explores the challenges faced by the author, such as the restriction of vocabulary and the need to preserve meaning in the absence of diacritics. Furthermore, the article examines the book's impact on Islamic thought, highlighting its strengths, such as the comprehensiveness of the exegesis, its spiritual depth, and its artistic authenticity, along with some weaknesses, such as the lack of practical examples and its difficulty for non-specialists. The article concludes that “Sawati Al-Ilham by Abu Al-faiz Faizi” is a valuable literary and spiritual reference that enriches the Islamic library, representing a unique experience in blending Qur'anic interpretation with rhetorical innovation. It is deserving of in-depth critical study for its stylistic novelty, intellectual richness, and its contemplative approach that enhances the spiritual meaning in interpretation. Keywords: Sawātiʿ al-Ilhām, al-Fayd Fayḍī, Characteristics, Neglected Style, Demonstrating, Contemplative, Interpretation